Improvement of extraction processing conditions for antifungal compounds from Alpinia galanga - Ahmad Raus, Raha; Addnan, Nor Hafizah; Mat Amin, Noriha; Aini Shohaimi, Syamsiah (IIUM Press, 2011)
Alpinia galanga IS a rhizomatous herbaceous perennial plant of the ginger family, Zingiberaceae that is known for its antifungal property. In this study optimization of extraction processing conditions were determined to obtain maximum yield of antifungal compounds from A. galanga. Optimization experiments designed by Box-Behnken (Design Expert Software) were carried out with three parameters considered namely agitation, extraction time and temperature. Analysis of results was done statistically using Analysis of Variance (ANOVA). The regression equation analysis showed that the optimum condition in producing antibacterial compound was temperature 2rC, time 11.3 hours and agitation level 323 rpm which gave the maximum diameter of zone inhibition (39.1 mm).